Narrative review of health‐related quality of life and its predictors among patients with coronary heart disease. Issue 1 (10th July 2014) - Muhammad, Imran; He, Hong‐Gu; Kowitlawakul, Yanika; Wang, Wenru
Abstract : This paper summarizes the empirical evidence concerning health‐related quality of life (HRQoL) of patients with coronary heart disease (CHD) and attempts to identify its significant predictors. A systematic search of the literature from 2002 to 2012 was conducted using seven electronic databases (CINAHL, ScienceDirect, Medline, Scopus, PsycINFO, PubMed and Web of Science) using the search terms 'HRQoL'. 'CHD', 'social support', 'depression', 'anxiety', 'psychosocial factors', 'sociodemographic factors', 'clinical factors' and 'predictors'. A total of 1052 studies were retrieved, of which 24 articles were included in this review. Previous studies have consistently demonstrated the negative impact of CHD on HRQoL, citing three major types of predictive factors: sociodemographic, clinical and psychosocial factors. Studies have also highlighted the advantageous use of HRQoL as a gauge for treatment satisfaction and efficacy. There are, however, few studies that collectively investigate the relationship among concepts such as HRQoL, anxiety and depression, social support, and sociodemographic and clinical factors in relation to CHD. This review highlights the need to conduct further study on HRQoL of patients with CHD in the Asian context. Such research will promote patient‐centric care and improved patient satisfaction through incorporation of the concept of HRQoL into clinical practice.